The Role of Innovation Capabilities in Mediating the Impact of Social Media Marketing and Business Networking on Msme Performance in West Kalimantan - Rudi, Jupensius Rudi; Murwani , F. Danardana; Suharsono, Naswan (AFEBI Management and Business Review, 2025)
This study examines the role of social media marketing, networking, and innovation capabilities in driving the marketing performance of food and beverage SMEs in West Kalimantan, Indonesia, using the Resource-Based View and Resource Advantage Theory. Data were collected from 100 SMEs and analyzed through structural equation modeling (SEM). The results show that SMM directly improves marketing performance, which is attributed to VRIN (valuable, rare, inimitable, non-substitutable) characteristics. Networking significantly improves innovation capability but fails to improve marketing performance directly due to structural barriers and generic innovations that do not have VRIN criteria. Innovation capability does not mediate the social media marketing. marketing performance relationship or the business network-marketing performance relationship. Resource Advantage Theory explains this by emphasizing the independent value of social media marketing in providing rapid market response, bypassing the need for innovation mediation. This study concludes that SMEs in resource-constrained regions such as West Kalimantan should prioritize optimizing social media marketing as a direct strategic asset and address infrastructure and collaborative gaps to unlock networking potential. The theoretical implications highlight the context-dependent application of RBV and the need for hybrid strategies that integrate digital tools with local cultural assets.